Characterization of Wave Fronts of Ultradistributions Using Directional Short-Time Fourier Transform - Atanasova, Sanja; Maksimović, Snježana; Pilipović, Stevan (MDPI AG, 2021)
In this paper we give a characterization of Sobolev k-directional wave front of order p∈[1,∞) of tempered ultradistributions via the directional short-time Fourier transform.